Effect of electric field on nucleation in undercooled melt. (5th July 2017) - Du, Lifei; Zhang, Limin; Zhang, Peng; Du, Huiling
Abstract: A revised nucleation theory in undercooled melt with applied electric field is derived based on the Classical Nucleation Theory, and the undercooling decrease caused by Joule heat release is also considered. The effect of applied electric field on the nucleation process in undercooling melts is calculated and discussed. Taking pure Al as the validation example, results indicate that with increasing electric field, the nucleation rate keeps increasing with a decreased undercooling, and the enhancement of nucleation rate caused by the electric field is the reason for grain refinement during solidification with electric treatment, which can be observed from the experimental investigation.